Indonesia’s Constitutional Immigration Policy: The Case of Rohingya Ethnic Group Refugees - Utami, Dian Wahyu; Saleh, Rahmat; Oktafiani, Irin (RMPI-BRIN, 2018)
In this increasingly dynamic world, international migration especially international refugee and asylum seeker has become a hot issue in many countries, including Indonesia. For example, a communal conflict between Rakhine and Rohingya ethnic groups in Myanmar in 2012 calls the attention of the international community, especially in Southeast Asia regions. The socio-political situation forced the ethnic minority Rohingya to leave Myanmar to move (migrate) or seek asylum to the neighbouring countries, such as Indonesia. In Indonesia, Rohingya refugees are mostly surviving in the boats “Manusia Perahu” camp in Aceh since 2015. The influx of refugees such as Rohingya into Indonesia constitutes a new problem in constitutional and social terms. This paper aims to explain Indonesia’s constitutional immigration policy and the public responses to asylum seekers taken from the case of Rohingya ethnic group in Indonesia. This study uses the literature review methods to explain the social problems and application of Indonesian regulations towards Rohingya refugees in the boats “Manusia Perahu” camp in Aceh. This study finds that a more explicit regulation is needed to regulate the entry of refugees, so that the locals will not be disturbed and still create security between countries.